SELECTION OF INDICATIVE INDICATORS OF ECOLOGICAL CONDITION OF SURFACE SOURCE OF WATER SUPPLY - Bezsonnyi, V. (Municipal economy of cities. Series: «Economy science», 2022)
In recent years, there has been an aggravation of problems in the field of environmental safety of surface water sources, which is caused by the unsatisfactory state of water resources. Among the reasons for this should be noted the lack of effective mechanisms for water management, control and responsibility. A comprehensive assessment of the environmental safety indicators of surface water sources of supply by chemical indicators is a laborious task. Indicators are obtained by combining and summarizing many complex indicators into one integrating one, which makes it possible to characterize different positions of water bodies. The practice of monitoring in surface water indicates the need to minimize resources to obtain a comprehensive assessment of the environmental safety of a water object. Therefore, the purpose of this work is to justify the choice as an indicative indicator of the ecological state of the surface source of drinking water supply of biochemical oxygen consumption. To do this, it is necessary to characterize the ecological state of the studied area using the combinatorial index of water pollution and establish a link between this index and biochemical oxygen consumption. The calculation of the value of the combinatorial pollution index and the relative assessment of the ecological state of surface water were carried out in two stages: first, for each individual investigated substance and indicator of the ecological state of surface water, then the entire complex of pollutants was considered simultaneously and the resulting assessment was derived. Baseline indicators play an important role in the ecology of a water object. Therefore, the content of dissolved oxygen and biochemical oxygen consumption in water is of great interest not only in terms of the development of life, but also as an indicative indicator of the ecological state of the aquatic environment, makes the indicator of biochemical oxygen consumption important for indicative assessment of water pollution by various organic substances. For the tasks for which we justify the choice of indicative indicators of the ecological state of surface water, it is more important to identify the consequences of pollution not directly at the site of pollution, but at some distance from it and after a while. Therefore, the use of the amount of dissolved oxygen and biochemical oxygen consumption as indicators characterizing the oxidation process of existing pollutants in water is the most appropriate for the tasks of operational monitoring of water bodies.